التثمين البيولوجي والصياغة الصيدلانية لمادة اللبن النباتي المستخلص من نباتي guyoniana Boiss.& Reut. Euphorbia , و Pergularia Tomentosa L. الناميين في منطقة وادي سوف - سقني خولة (Universty Of El-oued جامعة الوادي, 2025)
الملخص: تهدف هذه الدراسة التجريبية إلى تثمين الثروة النباتية الجزائرية من خلال تقييم الإمكانات البيولوجية والعلاجية والصياغة الصيدلانية لمادة اللبن النباتي لكل من نباتي اللبين Euphorbia guyoniana Boiss & Reut . (Euphorbiaceae) والغلقة (Asclepiadeceae) Pergularia tomentosa L الناميين في منطقة واد سوف. من خلال تقييم التأثيرات البيولوجية والدوائية في المخبر، وفي الجسم الحي من أجل النظر في الإمكانات العلاجية المحتملة في إدارة جروح الاستئصال وجروح الحرق في الجرذان. ولهذا الغرض؛ تم إجراء دراسة تشريحية لنبات E. gryoniana لتحديد توزع القنوات الافرازية لمادة اللبن النباتي، كما تحديد بعض الخصائص الفيزيو - فيتوكيميائية، إضافة إلى ذلك، تم تقييم بعض الأنشطة والتأثيرات البيولوجية والمتمثلة في تحديد النشاط المضادة للأكسدة، النشاط المضاد للالتهاب والنشاط المضاد للبكتيريا تجاه ستة سلالات ممرضة، كما تم حساب عامل الحماية من أشعة الشمس، بالإضافة إلى تدعيمها بدراسة في الجسم الحي، وتضمنت اختبار السمية الحادة للجلد لتركيبات الصيدلانية المحضرة من مستخلص اللبن النباتي الخام للأنواع المختبرة، وتقييم تأثيراتها الدوائية في إدارة علاج الجرح في الجرذان المستحث بالاستئصال والحرق واستناداً إلى النتائج المتحصل عليها كشف الفحص الفيتوكيميائي على العديد من المكونات النباتية بالإضافة إلى محتوى معتبر من عديدات الفينول الفلافونويد والتانينات المكثفة وإلى وجود العديد من المركبات الفينولية ذات الخصائص العلاجية المتنوعة، كما تظهر الفحوصات في المخبر، أن مستخلص اللبن النباتي لنباتي E, guyoniana و Promentosa، ذو كفاءة عالية كنشاطاً مضاداً للأكسدة وخاصة في مقايسة انحلال الدم واختبار بيتا كاروتين وإمكانات ناجعة كمضاداً للالتهابات، وإلى توفير حماية مقبولة لعامل الحماية من أشعة الشمس (SPF) والنشاط المضاد للبكتيريا تجاه السلالات البكتيرية المختبرة. ووفقا للنتائج التي تم الحصول عليها في الجسم الحي، أظهرت الجرذان المعالجة بمراهم EGLI و EGLII المحضرة من اللبن النباتي لنبات guyoniana في نموذج الاستئصال أقصر فترات تكوين الظهارة، حيث بلغت 16 و 12 يوما على التوالي. وكان معدل انكماش الجرح أعلى بشكل ملحوظ مقارنة بمجموعة الشاهد السلبي والمرهم البسيط ( Vaseline)، على الرغم من هذه الاختلافات لم تكن ذا دلالة إحصائية. كما أظهرت الجرذان المعالجة بمراهم PTLI و PTLII المحضرة من اللبن النباتي لنبات الـ P . tomentosa في نموذج الحرق إلى شفاء جرح حرق وإعادة إنبات بصيلات الفراء في مجموعتي PTLI و PTLII مقارنة بمجموعة الشاهد السلبية والمرهم البسيط ( Vaseline). وقد أسفرت عن وجود اختلافات ذات دلالة إحصائية جد عالية المعنوية بين PTLI و C (0.01) و p<0.001) OS) و PTLII و NC (p<0.01) OS & (p<0.01) في الختام، تقودنا النتائج المستخلصة من الدراسات في المخبر وفي الجسم الحي بأن مستخلص اللبن النباتي لكل من نباتي Eggoniana و P tomentosa ذا إمكانات بيولوجية واعدة، مما يعكس تأثيراته العلاجية الفعالة في تسريع شفاء وترميم الجروح الجلدية مما قد يفتح آفاقا جديدة كمصدر بديل فعال وأمن لعلاج الجروح Résumé : فرنسية أو انجلزية This experimental study aims to valorize Algeria's plant wealth by evaluating the biological and therapeutic potentials and pharmaceutical formulation of the latex obtained from the plants Euphorbia guyoniana Boiss. & Reut. (Euphorbiaceae) and Pergularia tomentosa L. (Asclepiadaceae) growing in the Oued Souf region. The study involved assessing the biological and pharmacological effects in vitro and in vivo to explore potential therapeutic applications in the management of excisional and burn wounds in mice. To this end, an anatomical study of E. guyoniana was conducted to determine the distribution of the secretion channels of the latex, alongside identifying some physicochemical properties. Additionally. various biological activities and effects were evaluated, including antioxidant activity, anti-inflammatory activity, and antibacterial activity against six pathogenic strains, as well as calculating the sun protection factor (SPF). This was complemented by in vivo studies, including acute skin toxicity testing for the pharmaceutical formulations prepared from the raw latex extract of the tested species and evaluating their pharmacological effects in managing excisional and burn wound healing in mice. Based on the obtained results, phytochemical screening revealed numerous plant components, along with moderate contents of polyphenols, flavonoids, and concentrated tannins, as well as the presence of several phenolic compounds with diverse therapeutic properties. Laboratory tests demonstrated that the latex extract of E. guyoniana and P. tomentosa exhibited high efficacy as an antioxidant, particularly in hemolysis assays and beta-carotene testing, with effective anti-inflammatory potential and acceptable sun protection factor (SPF) values against the tested bacterial strains. According to in vivo results, mice treated with EGLI and EGLII ointments prepared from the latex of E. guyoniana showed the shortest epithelialization periods in the Excisional Model, reaching 16 and 12 days, respectively. The wound contraction rate was significantly higher compared to the negative control group and simple ointment (Vaseline), although these differences were not statistically significant. Additionally, mice treated with PTLI and PTLII ointments prepared from the latex of P. tomentosa demonstrated enhanced healing of Burn Wounds and regeneration of hair follicles in groups PTLI and PTLII compared to the negative control group and simple ointment (Vaseline). Highly significant statistical differences were observed between PTLI and NC (p<0.01), OS (p<0.01), and PTLII and NC (p<0.01) & OS (p<0.01). In conclusion, the results derived from studies in the laboratory and in vivo suggest that the plant milk extracts of E. guyoniana and P. tomentosa have promising biological potentials, reflecting their effective therapeutic effects in accelerating the healing and repair of skin wounds. This may open new horizons as a safe and effective alternative source for wound treatment.
أطروحة دكتوراه تخصص بيولوجيا وفيزيولوجيا النبات في العلوم الطبيعة و الحياة
Keywords: النشاط المضاد للأكسدة النشاط المضاد للالتهاب النشاط المضاد للبكتريا الصياغة الصيدلانية الغالينوسية التئام الجروح. اللبن النباتي; Pergularia tomentosa L.; Euphorbia guyoniana Boiss. & Reut.; latex: HPLC; antioxidant activity; anti-inflammatory activity; antibacterial activity; galenic pharmaceutical formulation; wound healing.